Students’ Attitudes towards the Use of Smartphone for Language Learning Purposes - Wisnuwardana, Ignatius (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2019)
Utilization of smartphone technology and English language, emerging English language and smartphone technology in non-academic and academic activities for learning purposes, student’s perception towards the usage of smartphone apps for English learning purposes, and smartphone apps for enhancing English proficiency are the area where this study is focused, gained from Indonesian High School students. Two hundred participants from 10th-12th grader of private high schools in Surabaya - Indonesia participated by completing an anonymous questionnaire and 16 participants of each grade were randomly selected and interviewed to gain further understanding towards the findings. The findings indicated smartphone technologies are mostly used by the participants for communication and social media purposes. On the other hand, smartphone is also used incontrovertibly by participants for the certain educational purposes. In addition, learning English via smartphone mobile apps, and diverse types of teenager’s online activities were discovered, as well as area of their English skill improvement. The findings suggest that: the students are considerably enthusiastic for using apps to support learning and they also view that smartphones bring substantial potentials and should be optimized for learning through systematic and purposeful activities properly designed for school learning-related activities